Characteristics, Needs, and Help Seeking of Partner Violence Victims Mandated to Community Services by Courts and Child Protective Services. (28th October 2013) - Macy, Rebecca J.; Rizo, Cynthia F.; Ermentrout, Dania M.
Abstract : The rapid growth of a subpopulation of women victimized by intimate partner violence (IPV) garnered the attention of 2 human service agencies in 1 Southeastern United States city. These agencies noted a shift in their clientele from female IPV victims who voluntarily sought agency services to victims who were mandated to agency services by child protective services (CPS), the court system, or both. Court‐referred victims had been arrested for perpetrating IPV against their male partners. CPS‐referred victims were experiencing concerning levels of IPV in their families, whether or not the victim had ever perpetrated IPV. Moreover, this subpopulation of women tended to be primary caregivers of children. In response to the growth of this subpopulation, the agencies collaborated to design and implement a program targeting female IPV victims who were primary caregivers for their children and who had been mandated to the agencies' services. The research team partnered with the agencies to conduct an investigation of this community‐developed program and its participants. This article presents an exploratory, descriptive study that investigates (a) the characteristics of service‐mandated, parenting IPV victims; (b) the needs of service‐mandated, parenting IPV victims; and (c) the types of help‐seeking behavior these women had engaged in before their service referral. Study findings indicate that, although the participants showed parenting strengths and active help‐seeking efforts, this sample of women was characterized by severe IPV experiences and serious mental health needs.